2020
DOI: 10.3390/ijerph17197064
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia as a Mediator of the Effect of a Gerontogymnastics Program on Cardiorespiratory Fitness of Overweight and Obese Older Women: A Randomized Controlled Trial

Abstract: The objectives were to analyze the effect of a gerontogymnastics program on functional ability and fitness on overweight and obese older woman and to understand if sarcopenia mediates its effect. This randomized controlled trial involved 216 overweight and obese women. The experimental group (EG) carried out 12 weeks of a gerontogymnastics program. The assessment was of gait speed, cardiorespiratory fitness, functional capacity, and muscle strength. EG showed significant improvements in almost every test. When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 81 publications
(87 reference statements)
2
4
0
Order By: Relevance
“…The improvements observed in FC were similar to other studies [2,[35][36][37]. Boukabous et al [9] reported that VO2 peak improved after 2-4 weeks of exercise and cardiorespiratory fitness improved after 8 weeks [10].…”
Section: Discussionsupporting
confidence: 84%
“…The improvements observed in FC were similar to other studies [2,[35][36][37]. Boukabous et al [9] reported that VO2 peak improved after 2-4 weeks of exercise and cardiorespiratory fitness improved after 8 weeks [10].…”
Section: Discussionsupporting
confidence: 84%
“…The blood pressure in our study did not reach normative values with nine months of METP, which may indicate that older women with hypertension may need a longer period of exercise to achieve these values. The FC improvements observed were similar to those of Hortobágyi et al [22] and Marcos-Pardo et al [23]. After 8 months of METP, Blasco-Lafarga et al [24] reported improvements in lower body strength (20.23%), agility (22.32%), and aerobic capacity (14.54%), and Leitão et al [10] observed a 11.06% improvement in aerobic capacity after 9 months of MEP, both in normotensive older women.…”
Section: Discussionsupporting
confidence: 80%
“…A mean was calculated from 3 repetitions [ 37 ]. A digital grip strength dynamometer was used for this (TKK 5401; Takei Scientific Instruments Co., Ltd., Tokyo, Japan) [ 1 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, the European Working Group on Sarcopenia in Older People (EWGSOP) guidelines published in 2019 proposed a selection of diagnostic measures and cut-off points which can be used in clinical practice, including muscle strength, muscle mass and physical condition assessment [ 1 ]. The most commonly used methods to measure muscle mass loss are dual energy X-ray absorptiometry (DEXA) and bioelectrical impedance analysis (BIA), handgrip strength test (HG), short physical performance (SPPB) and gait speed [ 22 , 23 ]. The HG and time-up and go (TUG) tests are used in the diagnosis of sarcopenia [ 24 ].…”
Section: Introductionmentioning
confidence: 99%